2014
DOI: 10.1111/jsm.12241
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Questionnaire for Assessment of Dhat Syndrome: Development and Use in Patient Population

Abstract: Introduction Dhat syndrome is a culture-bound syndrome, characterized by the core belief of loss of semen accompanied by symptoms of general weakness, lack of energy and concentration, impaired sexual functions, and vague somatic troubles, often associated with an anxious or dysphoric mood state. Although many studies have described the clinical picture of Dhat syndrome, there is lack of availability of an instrument which can comprehensively assess patients presenting with Dhat syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 22 publications
(46 reference statements)
4
36
0
5
Order By: Relevance
“…Few previous studies conducted by Chaddha, et al, 14 Grover S, et al 15 and Gautam M, et al 16 reported that patients complaining of Dhat Syndrome are typically more likely to be young people, who are recently married or single; of average or low socio-economic status, coming from a rural area and belonging to a family with conservative attitudes towards sex while a study conducted by Verma R, et al 17 reported more prevalence from urban area.…”
Section: Discussionmentioning
confidence: 93%
“…Few previous studies conducted by Chaddha, et al, 14 Grover S, et al 15 and Gautam M, et al 16 reported that patients complaining of Dhat Syndrome are typically more likely to be young people, who are recently married or single; of average or low socio-economic status, coming from a rural area and belonging to a family with conservative attitudes towards sex while a study conducted by Verma R, et al 17 reported more prevalence from urban area.…”
Section: Discussionmentioning
confidence: 93%
“…Few previous studies conducted by Chaddha et al 12 , Grover S et al 13 and Gautam M et al 14 reported that patients complaining of Dhat Syndrome are typically more likely to be young people, who are recently married or single; of average or low socio-economic status, coming from a rural area and belonging to a family with conservative attitudes towards sex while a study conducted by Verma R et al 15 reported more prevalence from urban area…”
Section: Discussionmentioning
confidence: 96%
“…mass media, magazines, or Lay practitioners. Indigenous practices of medicine including Ayurveda reinforce the beliefs which increase distress associated with semen loss (Behere and Natraj, 1984;Bhatia et al, 1989;Bhatia and Malik, 1991;Deb and Balhara, 2013;Grover et al, 2014;Jhanjee et al, 2011;Malhotra and Wig, 1975;Nakra et al, 1977;Singh, 1985). As such it is assumed that patients with Dhat syndrome are misinformed about various aspects of semen formation.…”
Section: Introductionmentioning
confidence: 92%
“…The belief that loss of semen is the factor responsible for underlying physical and mental illness and sexual problems is the common thread in these subjects (Behere and Natraj, 1984;Bhatia et al, 1989;Bhatia and Malik, 1991;Grover et al, 2014;Jhanjee et al, 2011;Malhotra and Wig, 1975;Nakra et al, 1977;Singh, 1985). Patients attribute passage of Dhat to reasons such as masturbation and/or excessive indulgence in sexual activities, venereal diseases, urinary tract infections, overeating, constipation or worm infestation, disturbed sleep, or genetic factors (Bhatia and Malik, 1991;Grover et al, 2014;Jhanjee et al, 2011;Patil et al, 1996) Majority of the patients have been found to harbour associated masturbatory guilt (Behere and Natraj, 1984). Nakra et al (1977) found that patients with Dhat syndrome considered loss of semen as harmful, when compared to patients with sexual dysfunction.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation